Pengaruh Kompetensi dan Profesionalisme Kerja Terhadap Produktivitas Kerja dengan Dimediasi oleh Kepatuhan Terhadap Keselamatan dan Kesehatan Kerja di Proyek PT Elnusa Tbk - Rudi Fathurrohman; Edy Hartono; Dedi Muhammad Siddiq (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of Work Competence and Work Professionalism on Work Productivity, mediated by Compliance with Occupational Safety and Health (OSH/K3 Compliance), among employees of PT Elnusa Tbk projects. The method employed is quantitative with an explanatory research approach. Sampling was carried out using a Stratified Random Sampling technique, yielding 212 respondents whose data were then analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results indicate that Work Competence has a positive and significant effect on Work Productivity, and similarly, Work Professionalism also demonstrates a positive and significant effect on Work Productivity. Furthermore, the mediation test results prove that OSH Compliance plays a significant role in mediating the relationship between Work Competence and Work Productivity, as well as mediating the relationship between Work Professionalism and Work Productivity. Therefore, this study concludes that the increase in employee Work Productivity is highly influenced by their level of Competence and Professionalism, and this influence becomes stronger when supported by a high level of Compliance with Occupational Safety and Health standards in the project environment.